Optimization Design and Experiment of Integrated Planetary Carrier Transplanting Mechanism for Vegetable Seedling - Zhang Pengfei; Liu Dongmei; Zhao Xiong; Xu Yadan; Liu Dong (Jixie chuandong)
In order to simplify the transplanting mechanism of vegetable blanket seedlings and improve the transplanting efficiency, an integrated planetary carrier transplanting mechanism of picking and digging seedlings combined with non-circular gear planetary gear train and deformed elliptical planetary gear train is proposed to complete the working process of cutting, picking, sending, digging and throwing vegetable blanket seedlings. Firstly, according to the agronomic requirements of vegetable blanket seedlings, this study selects the appropriate transplanting trajectory, sets the accurate pose points, and establishes the kinematics model of the seedling pick-up mechanism by using the motion generation synthesis method. According to the motion trajectory requirements of the pick-up mechanism of seedlings, the relation curve of the input shaft and the output shaft rotation angle is obtained based on the parameter fitting optimization, and the total transmission ratio of the non-circular gear planetary gear train and the non-circular gear pitch curve parameters are calculated. Secondly, the optimization goal of the digging mechanism are determined and the parameters of the digging mechanism are obtained. Finally, the assembly of the whole mechanism combination and 3D model is completed, and the simulation and prototype test are carried out. The results show that the theoretical trajectory, simulation trajectory and test trajectory are basically the same. The average missed transplanting rate of seedlings is 2%, and the average lodging rate, injured seedling rate, and buried seedling rate are all 1.5%. All of them meet the agronomic requirements and the correctness of the mechanism design method is verified.